FISHERY AND BIOLOGY OF POMADASYS HASTA (BLOCK) - Deshmukh, V M (Indian Journal of Fisheries, 2011)
The Biology and Fishery of Pomadasys hasta (Bloch) has been described. The species exhibited single restricted spawning period during October to December. The minimumsizeof maturity was found to be 41.0 cm. The fish had shown intermittant feeding habit, feeding mainly on Crustacea like Squilla, crab and prawns and also Teleostean fish. Length-frequency and otolith data had been used to trace the growth and assess the age of the flsh. The growth rate was found to be 22.0 cm, in the first year^ 12.0 cm, each in the second and third years; 6.0 cm, and 4.0 cm in the fourth and fifth years respectively. The fishery for the species extended from September to June with a peak season in November to February. The Kutch and Dwarka regions were rich fishing grounds for the species.